2011
DOI: 10.2807/ese.16.10.19814-en
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgM and IgG antibodies to West Nile virus among blood donors in an affected area of north-eastern Italy, summer 2009

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
6
15
3
Order By: Relevance
“…West Nile Virus (WNV) is a member of the flaviviridae family and genus Flavivirus, transmitted by Culex mosquito species 1,2 . Birds are its natural host and they play a major role in the geographic dispersion of the virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…West Nile Virus (WNV) is a member of the flaviviridae family and genus Flavivirus, transmitted by Culex mosquito species 1,2 . Birds are its natural host and they play a major role in the geographic dispersion of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Plaque Reduction Neutralization Test (PRNT) was not done. This could have inflated the seropositivity for WNV since the cross reactivity of arboviruses was not taken into consideration, although another similar study which carried out the PRNT following the primary test showed that about 80% of the primary results were confirmed 1 . The other limitation could be the fact that the association of WNV and the veterinary and avian populations which exist in the provinces was not done.…”
mentioning
confidence: 99%
“…In the following years, cases of WNND were diagnosed in a larger area near the Po river [28,29,30], while sero-prevalence studies in blood and organ donors [31,32] and veterinary and entomological investigation indicated viral activity also in other regions [33]. This led the Italian Ministry of Health to publish in 2010 a national plan for WNND human surveillance that integrated veterinary and vector surveillance [13].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of surveillance in both animals and humans in the rural areas where the virus re‐emerged did not allow an accurate map to be made of West Nile virus circulation foci. This would have allowed the prediction of future outbreaks and an assessment of the risk of disease transmission through blood transfusion, although recent studies showed that blood donors living in risk areas should be systematically tested for West Nile virus infection (Pezzotti et al., ; Papa et al., ). In addition, the screening of sentinel wild bird species proved to be effective for identifying circulation areas (Jourdain et al., ).…”
Section: Socio‐economic Factorsmentioning
confidence: 99%